HCV genotype-3a T cell immunity: Specificity, function and impact of therapy - Humphreys, I; Von Delft, A; Brown, A; Hibbert, L; Collier, J; Foster, G; Rahman, M; Christian, A; Klenerman, P; Barnes, E (2012)
Background: Hepatitis C virus (HCV) genotype-3a infection is now the dominant strain in South Asia and the UK. Characteristic features include a favourable response to therapy; the reasons for this are unknown but may include distinct genotype-3a-specific T cell immunity. In contrast to genotype-1 infection, T cell immunity to this subtype is poorly defined. Objectives: The aims of the study were to (1) define the frequency, specificity and cross-reactivity of T cell immunity across the whole viral genome in genotype-3a infection and (2) assess the impact of interferon (IFN)-a/ribavirin on T cell immunity. Design: T cell responses in chronic and resolved HCV genotype-3a were analysed in comparison with genotype-1 infection (total n=85) using specific peptide panels in IFN-g ELISpot assays. T cell responses were followed longitudinally in a subset of genotype-3a infected patients receiving therapy. Responses were further defined by CD4 and CD8 subset analysis, sequencing of autologous virus and cross-reactivity of genotype-3a with genotype-1a/-1b antigens. Results: CD8 T cell responses commonly targeted the non-structural (NS) proteins in chronic genotype-3a infection whereas in genotype-1 infection CD4 responses targeting HCV core predominated (p=0.0183). Resolved infection was associated with CD4 T cells targeting NS proteins. Paradoxically, a sustained response to therapy was associated with a brisk decline in virus-specific and total lymphocyte counts that recovered after treatment. Conclusion: HCV genotype-3a exhibits a distinct T cell specificity with implications for vaccine design. However, our data do not support the theory that genotype-3a viral clearance with therapy is associated with an enhanced antiviral T cell response. Paradoxically, a reduction in these responses may serve as a biomarker of IFN responsiveness.